Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues explores Japan's experiences with past valued added tax (VAT) rate increases and discusses potential policy options to mitigate the economic impact of a third-rate increase. It assesses the impact on the Japanese economy and, where possible, provides some international context. Alongside possible mitigating policies, it also discusses the importance of policy commitment and credibility, and how they can influence the macroeconomic impact of tax rate changes. Carefully designing policy measures and communicating them clearly to the public are paramount to attenuate any negative outcomes in the short term. A simple, single-rate VAT would efficiently raise tax revenues and support the government's objective of achieving fiscal consolidation in the medium term. Assuming underlying macroeconomic conditions are favorable, the October 2019 VAT rate increase could potentially have a smaller impact on the economy relative to that of 2014 for several reasons. In order to reduce policy uncertainty and alleviate any adverse impacts from the 2019 VAT rate increase, the authorities should clearly communicate the timing and content of associated mitigating measures.